Microwave-extracted oil and oleoresin of ginger with and without solvent - Fitriany, Reniek (Animo Repository, 2008)
Ginger oil was extracted from the rhizomes of Zingiber officinale by steam distillation and microwave assisted extraction (MAE) with and without solvent. MAE with solvent (ethano) gave the highest yield of 5.30% followed by MAE without solvent of 0.37%. For steam distillation, the yield was only 0.18%. The GC-MS analyses of the extracts were also determined. The steam distilled and the MAE without solvent oils contained the following compounds: zingiberene, sesquiphellandrene, farnesene, phellandrene, nerolidol, geranial, curcumene and linalool. On the other hand, the MAE with solvent extracted oils contained zingiberene, the major volatile compound, and gingerol, the main non-volatile component. The MAE with solvent extracted oil is the oleoresin which was viscous and dark brown in color. Physicochemical tests of the steam distilled and MAE without solvent oils gave the following values: refractive index, 1.48; specific gravity (200), 0.86 and 0.89; acid values, 3.83 and 2.52; and ester values were 8.67 and 7.19 respectively. for the MAE with solvent (ethanol), the refractive index and ester value were not determined due to the color, the acid number was 0.012, and the specific gravity was 0.762. The antimicrobial activity test of the extracts showed that Bacillus subtilis (BS) was the most sensitive (72mm), followed by yeast Candida albicans (30mm). Staphylococcus aureus (25mm) and Escherichia coli (12mm) while Pseudomonas aerigonosa does not show any sign of sensitivity. The research on MAE with solvent showed that ethanol gave a higher yield compared to that of isopropanol. The yield of ginger extract increased with an increase of extraction time (1 to 6 min.), solvent/solid ratio (75/25 to 150/25 g/ml) and microwave power (400W to 600W). The shape of the reactor also showed significant effects on the yield in MAE with solvent.